METHODOLOGY OF AN ESTIMATION OF RELIABILITY OF THE INDUSTRIAL ORGANIZATION - V. N. Kabanov (Real Economics Publishing House, 2014)
The process methodology of an estimation of level of reliability of the industrial organization in modern market conditions of managing is considered. The theory of formation of level of reliability and competitive advantages of modern business structures on the basis of fundamental scientifically-practical aspects of system of market relations is stated. The economic-mathematical model of an estimation of level of reliability of production of the industrial organization as fundamental basis of construction of cybernetic models of diagnostics of economic system in the mathematician is presented.